Effects and safety of the traditional Chinese exercise baduanjin on depression and anxiety in COVID-19 patients: A systematic review and meta-analysis - Yan Huang; Xiao Xu; Bishal Kumar Chaurasiya; Prudence Bizimana; Mei-Juan Qian; Epipode Ntawuyamara (Elsevier, 2024)
Aim: This systematic review and meta-analysis aimed to assess the safety and efficacy of Baduanjin, a traditional Chinese exercise (TCM), for reducing depression and anxiety in individuals suffering from coronavirus disease 2019 (COVID-19). Methods: Nineteen databases were searched from their inception through August 2024 to gather data for this study. The focus of this study was randomized controlled trials (RCTs) in which Baduanjin was administered for the treatment of COVID-19 patients with depression and anxiety. The study included various types of Baduanjin exercise, whether used alone or in conjunction with other treatment modalities, for the control group. The comparators included a waitlist control, usual care, health education and supportive counseling, psychosocial support therapy, pharmacotherapies, and other common exercises. The exclusion criteria for trials were trials comparing different treatment durations, different treatment frequencies, and different types of Baduanjin exercise. Moreover, other traditional Chinese medicine (TCM) therapeutic methods applied in either the intervention or control group were also excluded. Throughout the entire study, the selection process, data extraction and quantitative analysis were carried out in strict adherence to all relevant guidelines. The Cochrane criteria for risk of bias were used to assess the methodological quality of the trials. In our review, a meta-analysis was performed using the software STATA MP14. Results: After conducting a meta-analysis, eight RCTs were found to have satisfied the inclusion criteria. The effects of Baduanjin exercise on self-rating anxiety scale (SAS) scores were investigated in five RCTs comprising a total of 228 patients. Analysis of the results revealed that the combination of Baduanjin exercises and conventional therapies led to a statistically significant reduction in SAS scores [MD=-3.21 (95 % CI= −3.64, −2.79), P< 0.001] compared to conventional therapies alone. Moreover, this systematic review explored the effect of Baduanjin exercise on self-rating depression scale (SDS) scores (three RCTs involving 83 participants), Hamilton Anxiety Rating Scale (HAM-A) scores (one RCT involving 103 participants), Patient Health Questionnaire (PHQ-9) scores (one RCT involving 70 participants) and Generalized Anxiety Disorder-7 (GAD-7) scores (one RCT involving 59 participants) for patients with COVID-19. The results showed that, in addition to conventional therapies, Baduanjin exercise had a more favorable impact on reducing the SDS score [mean difference (MD) =-2.86 (95 % CI=4.11, −1.61), P=0.025], PHQ-9 score [MD=-5.31, 95 % CI=-8.73, −1.89), P=0.002] and HAM-A score [MD=-3.00, 95 % CI=-5.33, −0.67], P=0.010] in patients with COVID-19 than did the use of conventional therapies alone. Furthermore, the combination of Baduanjin exercise and conventional therapies effectively decreased the number of patients who experienced severe or moderate anxiety according to the GAD-7 score compared to that of patients who experienced severe or moderate anxiety according to conventional therapies alone [Relative Risk (RR) =0.03, 95 % CI=0.00, 0.51); P=0.020]. However, the included clinical trials lacked a detailed description of the randomization process, and only a small portion of the studies reported proper allocation concealment procedures, which may introduce selection bias. Moreover, owing to the nature of Baduanjin exercise, it is difficult to blind participants and practitioners, which may lead to performance bias. Furthermore, the lack of blinding may lead to subjective influences of assessors on the results, thereby causing detection bias. These methodological shortcomings and potential biases should be addressed in future studies. Conclusions: It is difficult to draw firm conclusions on whether Baduanjin exercise is an effective intervention for reducing depression and anxiety in COVID-19 patients because of the high risk of bias among the available RCTs. Further rigorous RCTs are warranted but need to overcome the methodological shortcomings of the existing evidence.